Integrasi Nilai-Nilai Ulul Albab dalam Pendidikan Karakter sebagai Strategi Pembentukan Generasi Emas Indonesia 2045 - Ihsan Abdul Haq (Halaqa: Journal of Islamic Education, 2026)
This study is grounded in the urgency of strengthening character education amid increasing challenges of moral degradation, globalization, and rapid technological advancement that potentially weaken the character resilience of young generations. The purpose of this study is to examine the implementation and contribution of Ulul Albab valuesencompassing dhikr as spiritual reinforcement, fikr as intellectual development, and amal sholeh as the foundation of social ethics in character education to shape Indonesia’s golden generation of 2045 that is excellent and well-characterized. This research employs a qualitative approach using literature review and case study methods in educational institutions that apply Ulul Albab values. Data were collected through observation, in-depth interviews, and documentation, and subsequently analyzed using descriptive-analytical techniques. The findings indicate that the integration of Ulul Albab values in learning processes and character-building activities contributes to the formation of students who are religious, intelligent, possess integrity, and demonstrate strong social awareness. The discussion reveals that character education based on Ulul Albab values offers a holistic approach that is relevant to the needs of national character development in the contemporary era. The novelty of this study lies in the formulation of an integrative character education model that synergizes spiritual, intellectual, and social aspects in a sustainable manner. The policy implications of these findings emphasize the importance of formulating national education policies that systematically adopt Ulul Albab values through curriculum strengthening, enhancement of teacher competence, and educational management to support the realization of Indonesia’s Golden Vision 2045.